Atmospheric composition and thermodynamic retrievals from the ARIES airborne TIR-FTS system – Part 2: Validation and results from aircraft campaigns - G. Allen; S. M. Illingworth; S. J. O'Shea; S. Newman; A. Vance; S. J.-B. Bauguitte; F. Marenco; J. Kent; K. Bower; M. W. Gallagher; J. Muller; C. J. Percival; et al. (Atmospheric Measurement Techniques, 2014)
This study validates trace gas and thermodynamic retrievals from nadir infrared spectroscopic measurements recorded by the UK Met Office Airborne Research Interferometer Evaluation System (ARIES) – a thermal infrared, Fourier transform spectrometer (TIR-FTS) on the UK Facility for Airborne Atmospheric Measurements (FAAM) BAe-146 aircraft. Trace-gas-concentration and thermodynamic profiles have been retrieved and validated for this study throughout the troposphere and planetary boundary layer (PBL) over a range of environmental variability using data from aircraft campaigns over and around London, the US Gulf Coast, and the Arctic Circle during the Clear air for London (ClearfLo), Joint Airborne IASI (Infrared Atmospheric Sounding Interferometer) Validation Experiment (JAIVEx), and Measurements, process studies, and Modelling (MAMM) aircraft campaigns, respectively. Vertically resolved retrievals of temperature and water vapour (H 2 O), and partial-column retrievals of methane (CH 4 ), carbon monoxide (CO), and ozone (O 3 ) (over both land and sea) were compared to corresponding measurements from high-precision in situ analysers and dropsondes operated on the FAAM aircraft. Average degrees of freedom for signal (DOFS) over a 0–9 km column range were found to be 4.97, 3.11, 0.91, 1.10, and 1.62 for temperature, H 2 O, CH 4 , CO, and O 3 , respectively, when retrieved on 10 vertical levels. Partial-column mean biases (and bias standard error) between the surface and ~ 9 km, when averaged across all flight campaigns, were found to be −0.7(±0.3) K, −479(±56) ppm, −11(±2) ppb, −3.3(±1.0) ppb, and +3.5(±1.0) ppb, respectively, whilst the typical a posteriori (total) uncertainties for individually retrieved profiles were 0.4, 9.5, 5.0, 21.2, and 15.0 %, respectively. Averaging kernels (AKs) derived for progressively lower altitudes show improving sensitivity to lower atmospheric layers when flying at lower altitudes. Temperature and H 2 O display significant vertically resolved sensitivity throughout the column, whilst ...